Vegetation characteristics of Asian Tapir (Tapirus incidus) habitat in Way Kambas National Park - Jane Shafira Widodo; Abdul Haris Mustari (Talenta Publisher, 2026)
The Asian tapir (Tapirus indicus) is a protected, endemic species whose survival depends heavily on habitat conditions and quality. Way Kambas National Park is one of the important conservation areas in Sumatra. This study aims to quantify vegetation structure, species composition, potential food plant availability within Asian tapir habitats, and spatial distribution patterns of Asian tapir, conducted from January to February 2026. Data were collected through field observations and vegetation analysis. Vegetation analysis was conducted using 20 × 20 m line plots, totaling 50 plots. Asian tapir distribution data were obtained through line transect surveys and direct observations of signs such as footprints, feeding traces, feces, and wallows. The results indicate that Asian tapirs select habitats with high vegetation cover, abundant food availability, water sources, temperatures ranging from 27°C to 36°C, flat slopes (0–8%), and elevations of 25–50 masl. The spatial distribution of Asian tapirs forms a clustered pattern, as evidenced by 56 recorded signs of their activity. The findings also show a relationship between habitat characteristics and Asian tapir distribution, particularly the distance from water sources. Protecting secondary forests, maintaining food resources and water availability, and strengthening regular forest patrols are essential to support long-term Asian tapir conservation